Concise review: aerodynamic noise prediction methods and mechanisms for wind turbines - Vasishta Bhargava Nukala; Chinmaya Prasad Padhy (International Journal of Sustainable Energy, 2023)
Wind power plants are increasingly being installed across the world to combat energy deficits and climate change. One of the policy constraints for installing wind turbine plants is acoustic emissions from blades during operation. In this work, a concise review of the quasi-empirical methods important for predicting noise from rotating wind turbine blades is presented. For wind turbines, self-noise mechanisms from blades and random turbulent inflow noise sources influenced by atmospheric turbulence are two major classes which contribute to overall noise signature. It has been found that these sources exhibit narrowband and broadband frequency characteristics. Trailing edge noise from the blade is an important source at mid-band to high frequencies in overall noise spectra while at infrasonic and low frequencies, inflow and impulsive noise sources are dominant which produce high annoyance and harmful effects on inhabitants. Previous research findings related to self-noise mechanisms are discussed thoroughly to provide an insight of aerodynamically produced noise generation.